Sports injuries in indoor volleyball in people who play professionally and as a hobby - Alicja Mińko; Zuzanna Hilicka; Paulina Stępień; Zuzanna Bereda (Kazimierz Wielki University, 2021)
Introduction: Volleyball is a sport that causes injuries very often. They often result from the lack of an appropriate warm-up, the intensity of exercises that do not match the body's capabilities, or the use of inadequate techniques and poorly selected sports equipment. The aim of the study was to compare the injuries of people who play volleyball professionally with people who play volleyball. Material and methods: The research was conducted among 144 volleyball players - 75 women (52.08%) and 69 men (47.92%). They were in three age groups: 18-20, 21-25 and over 25 years of age. The group was divided according to the type of game, i.e. whether it is a professional (49.31%) or a hobbyist (50.69%). Each of the volleyball players completed the questionnaire. Results: The group playing volleyball professionally comprised 71 people (49.31%), while the amateur group comprised 73 people (50.69%). Among people professionally training volleyball, injuries were observed in 64 (90.14%) people, while among people training amateur volleyball, injuries occurred more often in as many as 70 (95.89%) people. The most common trauma in the first and second groups was sprain, which occurred in the first group in 27 (38.03%) people, and in the second group - 26 (35.62%). Conclusions: Sprains are the most common injuries among people who play volleyball professionally and as a hobby. Most people who play volleyball professionally after an injury benefited from rehabilitation.